Kewengan Judisial Badan Pengawas Pemilu Dalam Perspektif Asas Nemo Judex In Causa Sua - Agus Susanto (MLJ Merdeka Law Journal, 2020)
Authority of Bawaslu based on Law No. 7 of 2017, apart from the election administration supervisory body, it is also authorized to resolve disputes over the election process up to the District / City Bawaslu level. Authority is exercised by the Quasi-Court method. On January 23, 2019, an Election Process Dispute Request was registered by the Kasdi to the Bawaslu City of Bontang against the Bontang City KPU on the object of the dispute over Bontang City KPU Decree Number: 58/HK.03.1-Kpt/6474 KPU-Kot/IX/ 2018. The Bontang City KPU Decree is a follow-up to the East Kalimantan Bawaslu Decision Number 002/TM/PL/ADM/Prov/23.00/XII/ 2018 regarding the removal of the Kasdi's name in the DCT DPRD Bontang City Electoral District of Bontang 1 from the Nasdem Party. This research uses normative legal methods and conceptual approaches, to understand the concept of the principle of Nemo judex in causa sua in the Bawaslu Bontang Decision Number 01/PS.Reg/23.03/I/2019. The data source is secondary data. Normatively the Bawaslu judge of Bontang City has violated the principle of nemo judex in causa sua, but every decision issued by Bawaslu is final, final and binding. The decision must be accepted and implemented as a legal product. The juridical implication for judges who violate the principle of nemo judex in causa sua is that they are subject to administrative sanctions or being punished. Abstraks Kewenangan Bawaslu Berdasarkan UU No. 7 Tahun 2017 selain badan pengawas penyelenggaraan pemilu juga berwenang untuk penyelesaian sengketa proses pemilu hingga tingkat Bawaslu Kabupaten/Kota. Kewe-nangan dilaksanakan dengan metode Quasi Pengadilan. Pada tanggal 23 Januari 2019 telah didaftarkan Permohonan Sengketa Proses Pemilu oleh Kasdi ke Bawaslu Kota Bontang terhadap KPU Kota Bontang atas objek sengketa Surat Keputusan KPU Kota Bontang Nomor: 58/HK.03.1-Kpt/ 6474/KPU-Kot/IX/2018. SK KPU Kota Bontang tersebut adalah tindak-lanjut dari Putusan Bawaslu Provinsi Kalimantan Timur Nomor 002/TM/ PL/ADM/Prov/ 23.00/XII/2018 terkait pencoretan nama Kasdi dalam DCT DPRD Kota Bontang Dapil Bontang 1 dari Partai Nasdem. Penelitian menggunakan metode hukum normatif dan pendekatan konsep, untuk memahami konsep asas nemo judex in causa sua dalam Putusan Bawaslu Bontang Nomor 01/PS.Reg/23.03/I/2019. Sumber data berupa data sekunder. Secara normatif hakim Bawaslu Kota Bontang telah melanggar asas nemo judex in causa sua, namun setiap putusan yang dikeluarkan Bawaslu bersifat akhir, final dan mengikat. Putusan tersebut harus tetap diterima dan dilaksanakan sebagai produk hukum yang sah. Implikasi yuridis terhadap hakim yang melanggar asas nemo judex in causa sua ialah dikenakan sanksi administratif atau dipidana. DOI: https://doi.org/10.26905/mlj.v1i2.5495.